PROTECTIVE EFFECTS OF SELENIUM SUPPLEMENTATION AGAINST HIGH FRUCTOSE CORN SYRUP-INDUCED RETINAL DAMAGE IN RATS THROUGH REDUCTION OF INFLAMMATION AND APOPTOSIS - Usta, Gulsah; Savran, Mehtap; Özkaya, Dilek; Karaca, Umut; Karakuyu, Nasıf Fatih (International Journal of Retina, 2025)
Introduction: High fructose corn syrup (HFCS) consumption is associated with metabolic complications, including retinopathy. The aim of the current study is to investigate the potential protective effect of selenium (Se) against HFCS-induced retinal damage. Methods: Forty Wistar albino rats were divided into four groups (n=7 each): (I) control; (II) high fructose corn syrup (HFCS, 20% in diet); (III) HFCS + Se (20% in diet, 0.3 mg/kg orally); (IV) Se only. Retinal damage was assessed using histopathological (retinal thickness) and immunohistochemical (TNF-α, and Cas-3 expression) analysis. Results: Retinal thickness measurements revealed a significant increase in the HFCS group compared to the Control group, HFCS+Se group and Se group (all group, p<0.0001). Immunohistochemical analysis showed increased TNF-α expression in the HFCS group compared to the Control and Se groups (p<0.01), with a non-significant decrease in the HFCS+Se group (p > 0.05). Cas-3 expression was significantly increased in the HFCS group compared to the Control, Se groups (p<0.001 for both) and HFCS+Se group (p<0.01). Conclusion: Se supplementation partially protects against HFCS-induced retinal damage, particularly by reducing inflammation and apoptosis.